The Effect of Moringa oleifera Leaves and VipAlbumin® on The Immune System of Diabetes Mellitus Balb/C Mice Model - Almabrouk, Suheer Khalleefah; Dwi, Noviana; Rahayu, Sri; Rifaâ€™i, Muhaimin (Graduate School, Universitas Brawijaya, 2019)
Diabetes Mellitus is known as a disease grown worldwide rapidly prevalent day by day. This disease caused by a chronic hyperglycemic condition and also glucose intolerance resulting from defects in insulin secretion, insulin action, or both. Moringa oleifera is one of the plants used in most developing countries for traditional medicine for treating diabetes. In this research, Moringa oleifera mixed with VipAlbumin®, taken from snakehead fish albumin. Albumin found as an antioxidant against ROS. This research aimed to evaluate the effect of Moringa oleifera mixed with VipAlbumin® supplement towards the profile changing of T-cell, (CD4+ CD8+) B220+, CD4+ IFN-γ, and TNF-α. The experiments were done by dividing Balb/c mice into five groups and induced with 100 mg.BW-1 STZ. Afterward, the mix of Moringa oleifera and VipAlbumin® orally administrated into five different doses. Negative control contains of healthy mice, Positive dose administrated with 145 mg.kg bw-1 STZ, Dose 1 of 100 mg.kg bw-1 (Mo) + 416.25 mg.kg bw-1 (A), Dose 2 of 150 mg.kg bw-1 (Mo) + 208.15 mg.kg bw-1 (A), Dose 3 of 50 mg.kg bw-1 (Mo) + 624.375 mg.kg bw-1 (A). One way ANOVA was applied to analyze the data with p-value 0.05% and combined with Tukey test using SPSS version 16 for Windows. The results showed that a relative number of CD4 and CD8 T cells decreased in dose 3 of Moringa oleifera and Albumin, as well as B220 in dose 3 gave a significant decreased compared to healthy mice (p<0.05). The inflammation showed decreasing after treatment with dose 3 of Moringa oleifera and albumin extract. Taken together that proinflammatory cytokines decreased after treatment compared to a positive group. Keywords: Albumin, Inflammation, Moringa oleifera, T cells.